Purification of Crystals Protein by Aqueous Two Phase System fromBacillus thuringiensis Local Isolate - Jaafar, Mohammad; Al-Kazaz, Abdul Karrm; Mohammad, Ali (Iraqi Journal of Science, 2024)
The crystals protein of local isolate Bacillus thuringiensis were purified by usingaqueous two phase system method in two steps ; the first 94% of crystals protein andspores were separated from cell dibbers by using 14% g/ml ammonium sulphate and4% g/ml of Polyethylene glycol 6000 at pH=7 with separation time of 30 min.While in the second step, crystals protein were purified from spores by using asystem consisted of 8% g/ml Dextran 60000-90000 and 9% g/ml of Polyethyleneglycol 6000 at pH=7 with separation time of 2.5 h. the a final yield was 70.6% withpurity of 92%